Trends in inequality within countries using a novel dataset - Carlos Gradín; Annalena Oppel (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We revisit trends in within-country income inequality using a newly integrated dataset that covers at least 70 per cent of the global population since 1980. We investigate absolute and relative inequality trends across the past four decades, combining the use of Lorenz curves with a set of inequality measures to gain insights on countries without Lorenz dominance. We can conclude that the majority of the global population witnessed a robust increase in inequality in each decade, both absolute and relative, although the number of countries with evidence of declining relative inequality exceeds those with rising inequality in the 2000s and 2010s. Increasing absolute inequality is quite general, while evidence of increasing relative inequality is stronger in the 1990s and 2000s and weaker in the last decade and involves all country income groups. We found evidence of inequality levels converging over time, as well as of great heterogeneity across geographic regions.
Keywords: D31; E01; I31; O15; 330; within-country income inequality; integrated dataset